Jose Luna Castro's handbook of journalism - Castro, Jose Luna (Cacho Pub. House, 1990)
Purpose: This book "covers a wider field than a style book. It is addressed not only to the working newspaperman but also to the avid newspaper reader. Among other things, the latter needs to know how his daily news fare is prepared and how best to digest it. The updated classic on Philippine journalism by the respected journalist, with additional reflections or journalistic ethics and timely anticipations of the current revolution in communications technology."